PUBLIC ENGAGEMENT IN THE POLICY OF ARRANGEMENT AND EMPOWERMENT FOR STREET VENDORS IN GARUT KOTA SUBDISTRICT - Kurnia Muhamad Ramdhan; Budiman Rusli; Rd. Ahmad Buchari (Universitas Padjadjaran, 2020)
This paper aims to examine the cause of public engagement ineffectiveness in the policy of arrangement and empowerment for street vendors in Garut Kota subdistrict. The research method used is descriptive qualitative. Based on the results of the study, it can be concluded that public engagement in this policy has not been effective, because it has not been related to: 1) Context and Settings; 2) Sponsors, Conveners, and Their Motivations for Direct Public Engagement; 3) Process Design; and 4) Outcomes. Regarding Context and Settings, there are no specific rules for public engagement. Public engagement has become a formality to fulfill the principles of democratic governance, but most of the local government decisions and actions that are considered crucial in this policy do not represent street vendors desire. Regarding Sponsors, Conveners, and Their Motivations for Direct Public Engagement, public engagement in the policy does not have sponsors yet in its sustainability, as for those who are organizers of public engagement in this policy based on the Regent’s Decree, especially in the fields that give positions to street vendors to be engaged as implementing elements. Some information, related to Process Design and Outcomes, is challenging to obtain. In substance, the author does not find information that is genuinely relevant to the aspects contained therein. The author recommends that a comprehensive review be carried out to formulate the Implementation Guidelines and Technical Guidelines based on the elements set out in the framework of direct public engagement as a guideline for conducting public engagement.